LEARNING FROM EGYPT: An ‘Ulamâ’ Regeneration Initiative at MA Al-Azhar Asy-Syarif, North Sumatra - Dedi Sahputra Napitupulu; Ahmad Asrin (UIN Sumatera Utara, 2026)
The shortage of qualified ‘ulamâ’ in Indonesia remains a serious concern. This study examines the ulama regeneration initiative at MA Al-Azhar Asy-Syarif, which integrates the National, Cambridge, and Azhari curriculums. Using a qualitative design, data were collected through interviews, observations, and document analysis involving institutional leaders and curriculum managers. The findings show that curriculum planning is conducted collaboratively with academic validation from Al-Azhar University, producing a design that balances textual and rational sciences within the moderation paradigm. Implementation involves the use of classical texts, intensive language reinforcement, study circle activities, and a text-based learning model while responding to contemporary needs. Evaluation is carried out through continuous monitoring to maintain alignment with learning objectives and competency standards. The study demonstrates that the model offers strategic potential for strengthening ‘ulamâ’ regeneration in Indonesia. These findings contribute to curriculum management theory in Islamic education and provide practical insights for institutions engaged in developing future ‘ulamâ’.Keywors: Regeneration, ‘Ulamâ’, madrasah, Azhari Curriculum